Methods for assessing the burden of parasitic zoonoses: Echinococcosis and cysticercosis - Carabin, H.; Budke, C.M.; Cowan, L.D.; Willingham, Arve Lee; Torgerson, Paul R. (Elsevier, 2005)
Cysticercosis and echinococcosis cause illness and productivity losses in human and agricultural animal populations. Recent studies suggest that these diseases have large societal impacts on endemic areas. Estimates of burden provide essential, evidence-based data for conducting cost–benefit and cost–utility analyses that will secure political will, and financial and technical resources. To evaluate the burden, the monetary and non-monetary impacts of these zoonoses on human health, agriculture and society must be considered comprehensively. In this article, we review the framework used to assess the burden of cysticercosis and echinococcosis, and the data needed to estimate the extent of the problem for societies.